2011
DOI: 10.5800/gt-2011-2-4-0048
|View full text |Cite
|
Sign up to set email alerts
|

Mikhail M. Odintsov’s contribution to development of the mineral and raw materials complex of the Eastern Siberia

Abstract: The publication is devoted to the role of Mikhail M. Odintsov, Corresponding Member of the USSR Academy of Sciences, and his scientific school in solution of fundamental problems related to regularities of occurrence of endogenic mineral resources at ancient platforms. Based on mineragenic zonation data on the southeastern segment of the Siberian platform, Mikhail M. Odintsov determined the location of the AngaroViluisky ore belt that controls deposits and ore occur rences of magnetite, sulfates of copper and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…One source of iron or manganese could be the host rock, independent of microbially mediated processes. While according to Kadlec et al (2008) and Filippov (2000), no iron-bearing minerals are present in the host rock above the cave, it seems that early geological studies in the vicinity of the cave found sparse sulfide-rich deposits above the cave (Odintsev et al, 1947;Egorov, 2011). The reason why no iron oxides have been recorded since then remains unknown.…”
Section: The Host Rock As Potential Source Of Iron and Manganesementioning
confidence: 99%
“…One source of iron or manganese could be the host rock, independent of microbially mediated processes. While according to Kadlec et al (2008) and Filippov (2000), no iron-bearing minerals are present in the host rock above the cave, it seems that early geological studies in the vicinity of the cave found sparse sulfide-rich deposits above the cave (Odintsev et al, 1947;Egorov, 2011). The reason why no iron oxides have been recorded since then remains unknown.…”
Section: The Host Rock As Potential Source Of Iron and Manganesementioning
confidence: 99%